REIMAGINING ISLAMIC EDUCATION THROUGH LOVE-BASED PEDAGOGY: HUMANIZING CHARACTER FORMATION FOR INCLUSIVE SOCIAL TRANSFORMATION - Nurhafid Ishari; Muhammad Shodiq; Hafidhatur Rohmah (International Conference on Humanity Education and Society (ICHES), 2026)
Amid global challenges such as social fragmentation, moral alienation, and the instrumentalization of education, Islamic education has come under increasing criticism for placing too much emphasis on cognitive achievement and normative religiosity while failing to develop students' affective and humanistic capacities. This condition is particularly evident in many Muslim educational contexts, including madrasahs, where character education often remains prescriptive rather than transformative. Responding to this gap, this study reimagines Islamic education through love-based pedagogy as a way to humanize character formation and promote inclusive social transformation. Using a qualitative multisite phenomenological approach, this study explores the life experiences of teachers, students, and school leaders in selected madrasahs under the Indonesian Ministry of Religious Affairs. Data were collected through in-depth interviews, reflective journals, and participatory observation, and analyzed using thematic analysis based on humanistic perspectives and Islamic ethics. This methodological approach is increasingly used in contemporary educational research to capture the process of meaning formation and the affective dimensions of learning. The findings show that love-based pedagogy contributes to a deeper internalization of Islamic values, strengthens students' moral abilities, and fosters an inclusive attitude towards diversity. The novelty of this research lies in the positioning of love not only as a moral virtue but as a pedagogical framework based on Islamic ethics and contemporary humanistic education. This research offers theoretical and practical contributions by proposing an integrative model of Islamic character education that is in line with the global discourse on humanity and inclusion. Its implications highlight the potential of love-based pedagogy to inform curriculum development, teacher training, and policy innovation in madrasah education, advancing a more humane, inclusive, and socially responsive Islamic education system.